Selection for outbreeding in Varroa parasitising resistant honey bee (Apis mellifera) colonies. Issue 14 (1st July 2020) - Conlon, Benjamin H.; Kastally, Chedly; Kardell, Marina; Kefuss, John; Moritz, Robin F. A.; Routtu, Jarkko
Abstract: Parasitism is expected to select for counter‐adaptations in the host: driving a coevolutionary arms race. However, human interference between honey bees ( Apis mellifera ) and Varroa mites removes the effect of natural selection and restricts the evolution of host counter‐adaptations. With full‐sibling mating common among Varroa, this can rapidly select for virulent, highly inbred, Varroa populations. We investigated how the evolution of host resistance could affect the infesting population of Varroa mites. We screened a Varroa ‐resistant honey bee population near Toulouse, France, for a Varroa resistance trait: the inhibition of Varroa's reproduction in drone pupae. We then genotyped Varroa which had co‐infested a cell using microsatellites. Across all resistant honey bee colonies, Varroa's reproductive success was significantly higher in co‐infested cells but the distribution of Varroa between singly and multiply infested cells was not different from random. While there was a trend for increased reproductive success when Varroa of differing haplotypes co‐infested a cell, this was not significant. This suggests local mate competition, through the presence of another Varroa foundress in a pupal cell, may be enough to help Varroa overcome host resistance traits; with a critical mass of infesting Varroa overwhelming host resistance. However, the fitness trade‐offs associated with preferentially co‐infesting cells may be too high for Varroa to evolve a mechanism to identify already‐infested cells. The increased reproductive success of Varroa when co‐infesting resistant pupal cells may act as a release valve on the selective pressure for the evolution of counter resistance traits: helping to maintain a stable host–parasite relationship. Abstract : The evolution of host resistance is expected to select for counter resistance traits in a parasite. Here, we show evidence of selection for outbreeding in Varroa mites parasitising resistant honey bee pupae.